Information Quality of E-Government Websites as perceived by University Students in Pakistan - Tayyaba Rasool; Nosheen Fatima Warraich; Abebe Rorissa; Muzammil Tahira (Journal of Political Studies, 2018)
E-government websites are essential and effective modes of communication between governments and citizens and provide access to E-government services. Thus, information quality of these websites is vital and worth assessing in order to ensure their effectiveness. This study assessed the information quality indicators of egovernment websites in Pakistan as perceived by political science undergraduate students through a quantitative survey. This sample of students was selected because they are more likely to have used e-government websites to access information and/or receive services compared to other social science students. All the participants were 18 or more years old and computer literate. Data was collected through Kandari, Jones, Nah, and Bishu (2011) questionnaire adopted with minor changes. It had nine information quality indicators such as accessibility, authority, consistency, understandability, reliability, objectivity, navigation and efficiency; consisted of 21 statements. Respondents preferred to the point information on the websites along with proper and credible ownership for proprietary information. They also opined that information on e- government websites add value to their knowledge. Findings revealed that ‗accessibility‘, ‗authority‘, and ‗consistent and concise‘ were the top three indicators rated more than 4 on a 5-point Likert Scale. Overall, findings indicate a reasonably high information quality for Pakistani E-government websites as perceived by students. Findings will have implications relevant to user-centered design of E-government websites with respect to information quality.